Clinical and epidemiological features of chronic hepatitis C in the north-western region of Ukraine - T. I. Bevz (Journal of Education, Health and Sport, 2020)
HCV infection had become widespread all over the world. As a result of the constant registration of a significant number of new cases with a tendency to increase, high chronicity, risk of fatal complications, lack of specific prevention and the complexity of treatment, which is expensive, the problem remains one of the most important for global health. Due to the lack of official registration of acute hepatitis C in Ukraine until 2003, and chronic hepatitis C - until 2010, the data on the incidence by region are need to be supplemented. The paper presents data on the prevalence of hepatitis C among the population of Rivne region of the North-Western region of Ukraine.